Design optimization of broadband rape-based reflectary antena elements for x-band applications - Ijaz Malik, Hasan (2018)
This work focuses on analysis, design and optimization of broadband reflectarray antenna elements embedded on organic substrate materials. It addresses the key limitations of microstrip reflectarray antenna technology i.e., narrow bandwidth and high loss performance. It presents a novel dual resonance element with wide phase range and broadband frequency response for X-band reflectarray antenna. Multiple element design schemes have been simulated and analyzed for the identification of strategic element configurations using CST MWSV15. Three different paper substrate materials with controlled material compositions have been characterized using a broadband characterization technique. The characterization results demonstrated low permittivities of 1.81, 1.63 and 1.84 for the proposed dielectric substrates, along with loss tangents of 0.053, 0.048 and 0.057 respectively. Three different types of element configurations; rectangular, double C – Slot and double U – Slot were simulated over proposed paper substrate materials and fabricated using an adhesive copper tape. An infinite reflectarray embedded on a paper substrate was realized by using a waveguide simulator technique. An X-band tapered waveguide simulator was used for the scattering parameter measurements. Results for rectangular patch element fabricated over paper substrate show a reflection loss and phase range of -8.12 dB and 301º, with a 10% bandwidth of 340 MHz. A comparison of proposed design configurations signified that the double U – Slot element show promising results with a dual resonance behavior and wider phase range coverage. The double U – Slot element show resonance behavior at 7.61 and 11.05 GHz with a unified bandwidth of 815 MHz and a phase range of 602º. In order to establish a relation between the substrate height and reflection loss, a mathematical model has been established to estimate the reflection loss of elements fabricated above proposed substrate materials. Thus a promising bandwidth and wide phase range behavior, successfully demonstrates the use of organic substrate materials for an optimized microstrip reflectarray antenna.